In vivo study on the biocompatibility of chitosan–hydroxyapatite film depending on degree of deacetylation. Issue 6 (27th March 2017) - Jeong, Ki‐Jae; Song, Younseong; Shin, Hye‐Ri; Kim, Ji Eun; Kim, Jeonghyo; Sun, Fangfang; Hwang, Dae‐Youn; Lee, Jaebeom
Abstract: Chitosan, produced from chitin, is one of the polymers with promising applications in various fields. However, despite diverse research studies conducted on its biocompatibility, its uses are still limited. The main reason is the degree of deacetylation (DOD), which represents the proportion of deacetylated units in the polymer and is directly correlated with its biocompatibility property. In this article, the in vivo biocompatibility of three chitosan–hydroxyapatite composite films composed of chitosan with different DOD values was investigated by traditional biological protocols and novel optical spectroscopic analyses. The DOD of the chitosan obtained from three different manufacturers was estimated and calculated by Raman spectroscopy, Fourier transform infrared spectroscopy, and proton nuclear magnetic resonance spectroscopy. The chitosan with the higher DOD induced a higher incidence of inflammation in skin cells. The amino group density, biodegradability, and crystallinity of chitosan are the three possible factors that need to be considered when determining the biocompatibility of the films for in vivo application, as they led to complicated biological results, resulting in either better or worse inflammation even when using chitosan products with the same DOD. This basic study on the relationship between the DOD and inflammation is valuable for the development of further chitosan‐based researches. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 1637–1645, 2017.